Labor process and future relevance of the critique of capital - Neto, Benedito [UNESP] (Taylor & Francis, 2022)
The mistaken view that Taylorism-Fordism characterizes the most advanced form of the capitalist labor process reinforces an equally mistaken view of the relationship between capitalism and technology, known as ‘criticism of the productive forces’, which was very much in evidence in critical thinking throughout the 1960s and 1970s. Based on an analysis of three articles by a representative author of contemporary Marxist reflections upon the labor process, David Spencer, we will endeavor to show that these misconceptions remain extremely current, leading to an attitude that can be characterized as ‘Marxism-Luddism’. Given this outlook, the post-capitalist notion of labor as a fulfilling and free activity can only be understood as a ‘social epiphany’. We attempt to supersede this ‘social epiphany’ by identifying the opportunities generated by capitalism, and, from there, point out the fundamental theoretical locus for the future relevance of the critique of capitalism.
Keywords: capitalism; Labor process; Marxism; post-capitalism; productive forces